Implementation Of Tree Model In The Development Of E-Mantram Android Application - Sudana, Oka; Ivan M.J, I.W. Wahyu; Purnami S.P, Desy (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 13 No 2 (2022): Vol. 13, No. 2 August 2022DO - 10.24843/LKJITI.2022.v13.i02.p05, 2022)
Hindu Mantram is chants of speech with supernatural powers, which should not be done carelessly. The Balinese Hindu Mantram is a modified form of the Hindu Mantram that adapts to the local wisdom of the Balinese Hindu Community. The problem is that there is no digital education platform regarding the Balinese Hindu Mantram. Based on these problems, a mobile-based information system was built that integrates the Balinese Hindu Mantram and Yadnya Ceremony with its ceremonial procession. This information system applied Model Tree and UAT with PSSUQ Method. This research aimed to develop an application that can be a platform to provide education about the Balinese Hindu Mantram and its relationships. The results obtained from this research were the E-Mantram Android mobile application that implemented the Tree Model and UAT results with a System Usefulness value of 1.94, Information Quality of 2.06, Interface Quality of 2.06, and Overall of 2.01.